An Easy Primal Method for Geometric Programming - Ecker, J. G.; Zoracki, M. J. (Management Science, 1976)
A simple primal solution method for geometric programming is proposed. The method exploits the proximity of geometric and linear programming and is easy to implement by anyone having a linear programming code. Some examples and computational experience are given.